Clinical uses for omental tissue in the central nervous System - Hernando Rafael (2020)
Since 1978, clinical uses within the central nervous system have been found for omentum tissue, particularly in patients with ischemic conditions and/or ischemic penumbra. Omental tissue, one form of white adipose tissue (WAT), has some features that distinguish it from other WAT depots in other areas of the body. It is the best adipose tissue for developing vascular connections with surrounding tissue, and through these newly formed arterial blood vessels, nervous parenchyma may receive nutrients, oxygen, neurotransmitters, neurotrophic factors and stem cells. Moreover, the amount of adherent scar tissue in the omentalnervous system interface is minimal.